Synthetic and spectroscopic studies of novel nonplanar tetrapyrrolic macrocycles - Finnigan, Eimear M. (Trinity College (Dublin, Ireland). School of Chemistry, 2010)
The aim of this work was to develop a new synthetic route for the synthesis of hydroporphyrins and to investigate their photophysical properties. A second aim was to investigate the effect of protonation on the conformation of both porphyrins and hydroporphyrins.
Keywords: Chemistry, Ph.D.; Ph.D. Trinity College Dublin.